Flipped classroom strategies in biology learning: A systematic literature review - Muh. Wahyudi Jasman; S. Sulisetijono; Susriyati Mahanal (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Biology as an integral part of science learning continues to be maximized by integrating technology into its learning design. The definite manifestation of this integration process is to achieve meaningfulness, activeness, and effectiveness of the learning carried out. The flipped classroom (FC) is gaining popularity as a pedagogical model that uses the important benefits of technology in its learning environment. FC is proven to be an effective teaching mode that empowers students' 21st-century skills, stimulates students' self-learning, and improves academic performance. The potential of the FC is interesting to explore to what extent biology welcomes the FC. The aimed of this systematic literature review is to review and analyze articles published by Scopus indexed journals. We used the keywords "Flipped classroom and biology" in the search menu in the Scopus database and succeeded in finding 72 articles. There were 21 articles that met the criteria for further analysis. The inclusion and exclusion model used is PRISMA. The findings obtained are the trend of FC publications in biology learning over the last ten years. The approaches used in this research include quantitative, mixed method, case study and qualitative. Key words that are often used by writers are student, human, biology. The biology keyword has a branch, namely active learning. There are 9 countries of origin of authors who publish articles. The United States is a country that is active in publishing. Articles published on each continent are not evenly distributed. The dominant articles are published in collaboration with one country and rarely are articles published by one author. We have succeeded in formulating a picture of the existence of the FC in biology learning over the last ten years. These findings can be a consideration or reference for researchers to explore and study more deeply research related to the FC in biology learning based on their respective urgency.